Brain stimulation : methodologies and interventions - Reti, Irving (Irving M.) (Hoboken, New Jersey : Wiley Blackwell, 2015)
References; PART B: TECHNOLOGY; (1) Non-Invasive Brain Stimulation Modalities; (a) Convulsive; Chapter 5: Introduction to Convulsive Therapy; Introduction; The History of Convulsive Therapy; Electroconvulsive Therapy: Basic Principles; Electroconvulsive Therapy: Clinical Role; Magnetic Seizure Therapy (MST); Focal Electrically Administered Seizure Therapy (FEAST); Future of Convulsive Therapy; References; Chapter 6: Improving ECT Efficacy and Decreasing Cognitive Side Effects; Introduction; ECT Outcome Assessment: Therapeutic Efficacy and Cognitive Side Effects
Introduction to brain stimulation / Irving M. Reti and Andrew D. Chang -- A balanced mind : a network perspective on mood and motivation brain pathways / Morten L. Kringelbach -- Motor pathways, basal ganglia physiology and pathophysiology / Hagai Bergman, Shiran Katabi, Maya Slovik, Marc Deffains, David Arkadir, Zvi Israel, and Renana Eitan -- Viewing brain stimulation from a plasticity perspective / Jay M. Baraban -- Introduction to convulsive therapy / Richard D. Weiner -- Improving ECT efficacy and decreasing cognitive side-effects / Keith G. Rasmussen -- How does electroconvulsive therapy work? / Irving M. Reti -- Magnetic seizure therapy for the treatment of depression / Sarah Hollingsworth Lisanby, Zhi-De Deng -- Introduction to non-convulsive brain stimulation : focus on transcranial magnetic stimulation / Masashi Hamada and John C. Rothwell -- Advances in transcranial magnetic stimulation technology / Angel V. Peterchev, Zhi-De Deng, Stefan M. Goetz -- Applications of TMS to study brain connectivity / Gabriela Cantarero and Pablo Celnik -- Therapeutic applications of rTMS for psychiatric and neurological conditions / Mark S. George, E. Baron Short, Suzanne E. Kerns, Xingbao Li, Colleen Hanlon, Christopher Pelic, Joseph J. Taylor, Bashar W. Badran, Jeffrey J. Borckardt, Nolan Williams, James Fox -- Transcranial direct current stimulation : modulation of brain pathways and potential clinical applications / Michael A. Nitsche, R. Polania, M.-F. Kuo -- Epidural cortical stimulation / Ziad Nahas -- Neurological indications for deep brain stimulation / Jennifer J. Cheng, William S. Anderson, Frederick A. Lenz -- Psychiatric indications for deep brain stimulation / Reinier Prose, Damiaan Denys -- Vagus nerve stimulation for epilepsy and depression / Charles R. Conway, Mark A. Colijn, Steven C. Schachter.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Brain -- physiology; Deep Brain Stimulation -- methods; Electroconvulsive Therapy -- methods; Neural Pathways -- physiology; Transcranial Magnetic Stimulation; Brain -- Physiology; Electroconvulsive therapy; Neural networks (Neurobiology); MEDICAL / Physiology; SCIENCE / Life Sciences / Human Anatomy & Physiology; Brain -- Physiology; Electroconvulsive therapy; Neural networks (Neurobiology); Electronic books; Electronic books